2017
DOI: 10.1038/s41598-017-10471-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Immunosuppression on the Metagenomic Composition of the Intestinal Microbiome: a Systems Biology Approach to Post-Transplant Diabetes

Abstract: Solid organ transplantation (SOT) outcomes have continued to improve, although long-term use of immunosuppressants can lead to complications such as diabetes, compromising post-transplant outcomes. In this study, we have characterized the intestinal microbiome (IM) composition at the metagenomic level in the context of hyperglycemia induced by immunosuppressants. Sprague-Dawley rats were subjected to doses of tacrolimus and sirolimus that reliably induce hyperglycemia and an insulin-resistant state. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
69
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(69 citation statements)
references
References 44 publications
0
69
0
Order By: Relevance
“…There is a known association between GERD reflux and IPF. Many patients are on PPI which have been linked to an increased risk of pneumonia [21,39]. While we did not set out to address this issue prospectively, we demonstrated no association between GERD or PPI use and bacterial burden.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There is a known association between GERD reflux and IPF. Many patients are on PPI which have been linked to an increased risk of pneumonia [21,39]. While we did not set out to address this issue prospectively, we demonstrated no association between GERD or PPI use and bacterial burden.…”
Section: Discussionmentioning
confidence: 59%
“…The mean score between radiologists, following arbitration, was used as the final score for analysis. In general, there was a reasonable agreement between radiologists (Supplementary Table 3) [20,21]. Over half of the cohort had probable or definite UIP (57.7%) according to the current ATS/ERA/JRS/ALAT guidelines [13].…”
Section: Bacterial Burden and Radiological Disease Extentmentioning
confidence: 80%
“…Several studies have indicated their beneficial role in glucose homeostasis 14,17,18 . SCFAs activate de novo–synthesized glucose from the gut epithelium, which is sensed in the portal vein and participates in signaling through a gut–brain neural circuit to increase insulin sensitivity and glucose tolerance 19,20 . Furthermore, SCFAs promote the release of insulinotropic peptide hormones, including glucagon‐like peptide‐1 (GLP‐1) and peptide YY (PYY) secreted from enteroendocrine mucosal L cells, thereby restoring ÎČ‐cell insulin secretion and glucagon suppression 21‐23 .…”
Section: Introductionmentioning
confidence: 99%
“…MMF is stopped prior to embryo transfer because of its potential teratogenic impact, at which time it is usually replaced with azathioprine. Although there are no published data evaluating the VM following the induction of an immunosuppressed state, various studies have identified that the use of immunosuppression alters the intestinal microbiome in animals and humans, with subsequent normalisation of the intestinal microbiome seen following the administration of probiotics in the animal model . The currently accepted method of detecting rejection following UTx is by histological evaluation of cervical biopsies, which have been demonstrated to be consistent with rejection throughout the graft .…”
Section: Discussionmentioning
confidence: 99%